Education and training on the use of herbal medicines as complementary therapies for hypertension and diabetes - Muh. Agus Salim; Anjali Nurvitasari; Emy Suryani; Aisyah Fatimatul Khoeriyah; Lailiya Ramadanti; Feny Izzatul Latifah; Wiku Anjen Subekti (LPPM Politeknik Sandi Karsa, 2025)
Hypertension and diabetes mellitus are two non-communicable diseases with increasing prevalence in Indonesia, including in rural areas such as Kamulyan Village, Bantarsari Subdistrict, Cilacap Regency. Both conditions require long-term management using a holistic approach, including integrating complementary therapies based on medicinal plants. Unfortunately, community understanding of herbal medicine's proper and safe use remains limited. This community service program aims to improve the knowledge and skills of residents in Kamulyan Village in utilising herbal remedies as complementary therapy for hypertension and diabetes mellitus. The implementation methods included health education sessions on the introduction of hypertension and diabetes, as well as education on various types of local medicinal plants that are empirically proven to help control blood pressure and blood glucose levels, such as bay leaves (Syzygium polyanthum), bitter leaf (Andrographis paniculata), Phyllanthus niruri, cat’s whiskers (Orthosiphon aristatus), and Tinospora crispa. In addition, practical training was conducted on preparing and processing these herbs into simple formulations that can be used independently at home, such as herbal teas, decoctions, and dried capsules. The activity was attended by 50 participants: health cadres, elderly residents, and patients with hypertension and diabetes. Through pre-test and post-test assessments, participants’ knowledge and skills related to herbal medicine usage were significantly increased. Participants also demonstrated high enthusiasm for cultivating and utilizing family medicinal plants (TOGA) around their homes. This initiative is expected to be the first step toward community self-reliance in maintaining health naturally and sustainably. In the future, further assistance and cross-sector collaboration are needed to develop the scientific, safe, and effective use of herbal medicine at the community level.